Radiotherapy in Inoperable Mucoepidermoid Parotid Cancer: A Case Report - Steven Octavianus; Henry Kodrat (Indonesian Journal of Cancer, 2021)
Introduction: Salivary gland cancer is an uncommon malignancy in the head and neck. The most common histopathologic type in salivary gland malignancies is mucoepidermoid carcinoma (MEC). Radiotherapy has a role in salivary gland malignancy, especially in inoperable cases and postoperative settings. Definitive or postoperative radiotherapy with or without chemotherapy can improve locoregional control (LRC) in patients with parotid mucoepidermoid carcinoma. Case Presentation: We report a case of a 77-year-old male with inoperable MEC of the right parotid, who received definitive radiotherapy. From the three-month evaluation after radiation therapy, we found a significant reduction in the tumor mass. Conclusions: Surgery remains the treatment of choice for patients with salivary gland malignancies. Definitive radiotherapy can be a treatment modality in inoperable cases or patients who refuse surgery. Although the result is not satisfactory, radiotherapy can still give clinical benefits to patients.